2004
DOI: 10.1079/sum2004274
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil quality due to introduction of broad-leaf trees into clear-felled Chinese fir forest in the mid-subtropics of China

Abstract: SUMMARYEcological regionalization is a base for rational management and sustainable utilization of ecosystems and natural resources. It can provide a scientific basis for constructing healthy ecological environments and making policies of environmental management. In this paper, based on synthetic analysis of the characteristics of the ecology and environments of China, the principles of ecological regionalization are discussed, and indices and nomenclature of ecological regionalization are proposed. The ecore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Thus, the higher metabolic quotient (qCO 2 ) in pure plantations reflects a decrease in the efficiency of substrate utilization by soil microbial community. The low microbial C utilization in pure Chinese fir plantation soil was consistent with the results of Huang et al (2004). There was a negative correlation between the qCO 2 and soil pH in Chinese fir plantations (r = 0.216, n = 18), and the soils under mixed plantations had a higher pH values than that under pure plantation (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the higher metabolic quotient (qCO 2 ) in pure plantations reflects a decrease in the efficiency of substrate utilization by soil microbial community. The low microbial C utilization in pure Chinese fir plantation soil was consistent with the results of Huang et al (2004). There was a negative correlation between the qCO 2 and soil pH in Chinese fir plantations (r = 0.216, n = 18), and the soils under mixed plantations had a higher pH values than that under pure plantation (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the contribution of microbial C to soil organic C in natural secondary broad-leaved forest was higher than in C. lanceolata plantations (Table 2). This result agrees with the observations reported by Xu and Xu (2003), and was very low compared to the values reported from subtropics forest soils (Huang et al 2004), tropical forest soils (Dinesh et al 2003;Salamanca et al 2006). The contribution of microbial N to total N also had significant difference between natural secondary broad-leaved forest and C. lanceolata plantations, which falls within the reported range of forest soils (Martikainen and Palojarvi 1990) and agricultural soil) (Brookes et al 1985b), but was much higher than the observation reported by Dinesh et al (2003) and Devi and Yadava (2006) for tropical forest soils.…”
Section: Discussionsupporting
confidence: 93%
“…The microbial quotient was calculated using the ratio of microbial biomass carbon to soil organic carbon. It can provide an early warning of the improvement or deterioration of soil quality (Huang et al 2004). All analyses were conducted in triplicate and expressed on the basis of ovendry weight of soil (105°C, 12 h), and the means were taken as representative values for the measured soil properties.…”
Section: Soil Analysismentioning
confidence: 99%